(untitled) (Raparin Journal of Humanities (RJH), 2023)
Psycholinguistics consider that a comprehension is a process of interaction among reader, text and the surrounding culture. In this process the reader creates meaning and the clarity of the text depends on the language as well as the types of the reader and the quality of the text. In teaching process, the reader is pupil and the text is the written forms in tutorial books. It is important to be known that the language should be clear. The decision about readability and unreadability of a tutorial text has its criterion. In this frame the text book of Economic in the twelfth grade is taken as a sample and assessed in the viewpoints of pupils in a comprehensive assessment process. One of the ways of assessment is to use a questionnaire method in which pupil’s comprehension is detected. This research puts a questionnaire about a written language in Economic twelfth grade book. The pupil’s comprehension is assessed through answering, as a result the readability of the text is determined. Thus It shows that the readability of the text is in a lower level.